Crosstalk between fat tissue and muscle, brain, liver, and heart in obesity: cellular and molecular perspectives - Zixuan Jia; Ziqi Wang; Huixin Pan; Jing Zhang; Qinglu Wang; Caixia Zhou; Jun Liu (European Journal of Medical Research)
Abstract A high-fat diet and physical inactivity are key contributors to obesity, predisposing individuals to various chronic diseases, such as cardiovascular disease and diabetes, which involve multiple organs and tissues. To better understand the role of multi-organ interaction mechanisms in the rising incidence of obesity and its associated chronic conditions, treatment and prevention strategies are being extensively investigated. This review examines the signaling mechanisms between different tissues and organs, with a particular focus on the crosstalk between adipose tissue and the muscle, brain, liver, and heart, and potentially offers new strategies for the treatment and management of obesity and its complications.